2005
DOI: 10.1111/j.1469-8986.2005.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

A freezing‐like posture to pictures of mutilation

Abstract: Postural sway and heart rate were recorded in young men viewing emotionally engaging pictures. It was hypothesized that they would show a human analog of "freezing" behavior (i.e., immobility and heart rate deceleration) when confronted with a sustained block of unpleasant (mutilation) images, relative to their response to pleasant/arousing (sport action) or neutral (objects) pictures. Volunteers stood on a stabilometric platform during picture viewing. Significantly reduced body sway was recorded during the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
255
4
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 279 publications
(300 citation statements)
references
References 33 publications
33
255
4
8
Order By: Relevance
“…In the present study, however, we observed potentiation of an interference effect during a non-emotional, simple visual detection task performed when the affective stimulus was not being displayed. In this context, it is noteworthy that Azevedo et al (2005) revealed a gradual slowing down of heart rate when subjects viewed the same unpleasant pictures as employed in the present study (the gradual slowdown appeared to asymptote around the 5-6th picture presentation). These results suggest a gradual instatement of an emotional state, which may underlie the interference effect observed in the present study.…”
Section: Time Course Of Modulatory Effectssupporting
confidence: 50%
See 1 more Smart Citation
“…In the present study, however, we observed potentiation of an interference effect during a non-emotional, simple visual detection task performed when the affective stimulus was not being displayed. In this context, it is noteworthy that Azevedo et al (2005) revealed a gradual slowing down of heart rate when subjects viewed the same unpleasant pictures as employed in the present study (the gradual slowdown appeared to asymptote around the 5-6th picture presentation). These results suggest a gradual instatement of an emotional state, which may underlie the interference effect observed in the present study.…”
Section: Time Course Of Modulatory Effectssupporting
confidence: 50%
“…Moreover, humans evoke robust physiologic reactions when viewing mutilation pictures ). More importantly, in a recent experiment from our group (Azevedo et al, 2005), male subjects viewed the exact same sequence of mutilation and neutral pictures as in the present study while posturographic and electrocardiographic recordings were acquired. The results revealed a freezing-like state consisting of immobility, rigidity and bradycardia when viewing unpleasant relative to neutral pictures.…”
Section: Unpleasant Stimuli and Sustained Task Interferencementioning
confidence: 97%
“…Neural processing of unpleasant and threatening items proceeds in a stereotypical manner; the initial response is typically postural immobility, during which the organism is hypervigilant (e.g. [2,16,17]). This response is then followed by overt action patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Posturographic studies have revealed that potent emotional triggers may activate innate behavioral tendencies, such as freeze, fight, or flight responses [2][3][4]. These responses may play into the neural control of balance, where they become visible as automatic postural adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…A significant rise of the skin conductance level can be found for both positive and negative stimuli when compared to neutral ones (e.g., Azevedo et al, 2005;Bradley et al, 2001Bradley et al, , 2005.…”
Section: Emotional Scenesmentioning
confidence: 99%